Encontros e desencontros no paraíso: etnografia de relações afetivo-sexuais entre pessoas locais e turistas estrangeiras(os) em Jericoacoara-Ceará, Brasil - Martins, Helenita Maria Teixeira Marques (2024)
The objective of this dissertation, of an anthropological nature, sought to understand, based on an ethnography carried out in Jericoacoara, Ceará, using eight narratives about affective-sexual relationships between local and foreign people, how bonds are built and, at the same time, at the same time, emotional conflicts and how these were shaped in the lives of these people. It is also considered how the notion of temporality of relationships and mobility inside and outside the tourist location influence the affective and emotional perceptions of these people. The village of Jericoacoara is a tourist destination among the most sought after nationally and internationally, for this reason relationships have this location as a point of connection, however, they occur when traveling through countries in Europe, North America or even other cities in Brazil. The methodology included in-depth interviews, informal conversations and field observations over two years of research, through which I understood how these people, in their reports, expressed different emotions and feelings in their reports about the affective-sexual relationships that they maintained in their interactions in tourist places or when they were on the move. The information gathered from these meetings and interviews revealed the relevance of the emotional dimension and the emotional bond in the situations monitored. Anthropological studies on sexual tourism as a phenomenon of affective-sexual interactions in tourist locations and the possibilities of sex markets in migration contexts emphasize, with rare exceptions, the understanding of relationships with a focus on economic relations and material benefits that the sexual encounter between tourists and locals produce. Otherwise, based on the narratives presented in this research, it is possible to understand that the affective dimension overlaps, at various stages of the relationship, the material dimension, that is, financial and material gains. Thus, the symbolic understanding of affective-sexual relationships, presented here with a focus on emotions and conflicts, contributes to the studies of sexualities experienced in tourist locations, both locally and globally.